2015
DOI: 10.1160/th14-09-0771
|View full text |Cite
|
Sign up to set email alerts
|

Zinc delays clot lysis by attenuating plasminogen activation and plasmin-mediated fibrin degradation

Abstract: Zinc circulates free in plasma at a concentration of 0.1-2 µM, but its levels increase locally when it is released from activated platelets. Although zinc influences many processes in haemostasis, its effect on fibrinolysis has not been thoroughly investigated. Using a fluorescent zinc-binding probe, we demonstrated that zinc binds tissue-type plasminogen activator (tPA) and plasmin with high affinity (Kd values of 0.2 µM), and surface plasmon resonance studies revealed that zinc binds fibrin with a Kd of 12.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(50 citation statements)
references
References 40 publications
0
49
0
Order By: Relevance
“…Primarily using mouse models, Shannon et al [63] showed that HRG interacts with fibrin filaments at the wound site in order to capture and prevent the escape of invading bacteria systemically. Notably, this interaction of HRG with fibrin is Zn 2+ -dependent, which acts as the cofactor between these binding partners [27,61,63]. In addition, an infection model of S. pyogenes (AP1 strain) in HRG -/- mice resulted in a marked reduction in survival rate, when compared to wild type.…”
Section: The Antibacterial and Antifungal Properties Of Hrg At Sitmentioning
confidence: 99%
See 4 more Smart Citations
“…Primarily using mouse models, Shannon et al [63] showed that HRG interacts with fibrin filaments at the wound site in order to capture and prevent the escape of invading bacteria systemically. Notably, this interaction of HRG with fibrin is Zn 2+ -dependent, which acts as the cofactor between these binding partners [27,61,63]. In addition, an infection model of S. pyogenes (AP1 strain) in HRG -/- mice resulted in a marked reduction in survival rate, when compared to wild type.…”
Section: The Antibacterial and Antifungal Properties Of Hrg At Sitmentioning
confidence: 99%
“…Alternatively, the acidic pH and/or Zn 2+ may simply be regulating plasmin activity. The latter has been suggested, as a recent study demonstrates that Zn 2+ is capable of interacting with plasmin, t-PA and u-PA to reduce their activities and subsequently attenuate clot dissolution [27]. In addition, an acidic milieu has been shown to almost completely inhibit plasmin activity [50].…”
Section: Plasmin-mediated Cleavage Of Hrg Alters Its Biological Fumentioning
confidence: 99%
See 3 more Smart Citations